Echocardiographic parameters related to pulmonary arterial hypertension in patients with chronic myeloid leukemia under dasatinib treatment: Parámetros ecocardiográficos relacionados a hipertensión arterial pulmonar en pacientes con leucemia mieloide crónica en tratamiento con dasatinib - Poot Noh, Karla (2021)
Introduction: The use of dasatinib in patients with CML has improved life expectancy and follow-up with transthoracic echocardiography (ECOTT) for early detection of PAH allows modifications to the treatment. Objective: To determine the echocardiographic parameters and echocardiographic probability for PAH in patients with CML treated with dasatinib. Methods: Correlation, cross-sectional, retrospective, single-center study; patients with CML treated with dasatinib were included. Spearman and Pearson correlation was used. Results: 16 patients were analyzed, mean age 53.5 years; 62.5% men, 37.5% women. The dasatinib dose was 50 mg / day in 18.7%, and 100 mg / day in 81.2%, mean pulmonary arterial pressure (mPAP) 26.3 mmHg, mean maximum tricuspid regurgitation velocity (VmxRT) 2.9 m / s, mean pulmonary artery systolic pressure (PSAP) 41 mmHg. 56.2% had right ventricular diastolic dysfunction (RVDD). 43% were categorized as low probability for PAH, 18.7% intermediate, and 37.5% as high. Relationship between PAPm and VmxRT with p = 0.012. Relationship between mPAP and RV diastolic function, with p = 0.002. Relationship between probability for PAH and mPAP, with p = 0.008. Conclusion: The echocardiographic parameters PAPm, VmxRT, PSAP, DDVD and echocardiographic probability for PAH are useful and necessary for the diagnosis of PAH. The determination of all these parameters should be carried out early and as a follow-up, since a considerable positive relationship was found for each one with the presence of PAH, which is not dependent on the treatment time or the dose of dasatinib.